Challenges of Teaching and Learning Writing Skills in Nepalese English Classes - Bhandari, Bhim Lal (Tribhuvan University Journal, 2024)
Writing is one of the important language skills that most language learners want to acquire to write effectively in different contexts. It is to be mastered in learning English as a foreign language as it is a challenging task and the mastery of the English language. This article aims to explore the English language teachers’ and students’ challenges with teaching and learning writing skills in Nepali English classes of Nepal. To achieve the objective of the study, I used a survey research design. I selected eighty respondents (twenty teachers and sixty students) randomly from ten public schools in Rupandehi, Nepal. Two sets of closed-ended questionnaires with 24 items were used as a major technique to collect data about teaching and learning writing in terms of problems. The findings of the study showed that the majority of school students faced challenges in learning writing skills due to a lack of vocabulary, difficulties with syntax, unethical spelling and punctuation, lack of exposure and motivation, an adverse family environment, and incompetence in arranging phrases and paragraphs. Similarly, the majority of the teachers faced challenges in motivating the students, and preparing suitable activities for different writing tasks in the class. The results of this study can aid in understanding the difficulties that teachers and students have while teaching and learning writing skills.